ANALISIS KINERJA KEUANGAN PERUSAHAAN DAERAH AIR MINUM TIRTA MAKMUR KABUPATEN SUKOHARJO BERDASARKAN KEPUTUSAN MENTERI DALAM NEGERI NO. 47 TAHUN 1999 - Endah Tri Winarni, Djoko Kristianto & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research is to analyze the level of financial performance PDAM Tirta Makmur Kabupaten Sukoharjo during the fiscal year 2013-2014 based on Kepmendagri No. 47 in 1999. Research methods method using case studies in PDAM Tirta Makmur Kabupaten Sukoharjo, the types of data the data used was qualitative and quantitative data, the source data used the data of second. Method of data collection used documentation. Technique of data analysis using quantitative descriptive analysis that is doing the financial performance assessment calculation PDAM Tirta Makmur Kabupaten Sukoharjo based on the decision of the Minister of the Interior No. 47 in 1999. The research results obtained the conclusion that the assessment of the financial performance at the PDAM Tirta Makmur Kabupaten Sukoharjo 2013 obtained a score of 49 and in 2014 acquired a score of 45 are on the range of value of more than 42, it means including the criteria well. Thus the assessment of financial performance PDAM Tirta Makmur Kabupaten Sukoharjo based on decision letter of the Minister of the Interior No. 47 of 1999 on guidelines for the assessment of financial performance TAPS issued by Minister of the Interior based on the decision letter of the Minister of the Interior No. 47 in 1999 entered the category very well.Keywords: financial performance, financial ratio